TECHNICAL RISK PROFESSIONAL ASSESSMENT METHOD IMPLEMENTED IN SMALL AND MEDIUM-SIZED ENTEPRISES (SMEs) - TOTH (MIHĂILĂ), Nicoleta-Voichiţa; BORZAN, Marian (Studia Universitatis Babeş-Bolyai Bioethica, 2017)
This paper presents a new technique for identifying hazards and assessing risks of injury specific to professional employment in any type of organization. This evaluation method comprises three sections, namely: a) Analysis of the risk of work accidents and professional diseases at workplace / activity performed within the analysed area along according to operational characteristics applicable at the time (date) of performing the analysis; b) Analysis of the risk of accidents and professional diseases, resulting from the proposed prevention and protection measures applicable; c) Implementation of measures of prevention and protection and carrying-out an analysis through reassessment of the level of risk of injury and occupational disease. REZUMAT. În lucrarea de față este prezentată o nouă tehnică de identificare a pericolelor și evaluare a riscurilor de accidentare profesională specifică locurilor de muncă din oricare tip de organizație. Această metoda de evaluare cuprinde trei secţiuni și anume: • analiza nivelului de risc de accidentare şi îmbolnăvire profesională, existent la locul de muncă / activitatea prestată în zona analizată, cu caracteristicile de execuţie existente la momentul (data) analizei; • analiza nivelului de risc de accidentare şi îmbolnăvire profesională, rezultat în urma propunerii de măsuri de prevenire şi protecţie, aplicabile; • aplicarea măsurilor de prevenire şi protecţie şi analiza prin reevaluare a nivelului de risc de accidentare şi îmbolnăvire profesională. Cuvinte cheie: sănătate și securitate la locul de muncă, nivel de risc, identificarea riscului, măsuri de control.